2021
DOI: 10.3390/cells10102773
|View full text |Cite
|
Sign up to set email alerts
|

Coactivation of GSK3β and IGF-1 Attenuates Amyotrophic Lateral Sclerosis Nerve Fiber Cytopathies in SOD1 Mutant Patient-Derived Motor Neurons

Abstract: Amyotrophic lateral sclerosis (ALS) is a progressive nervous system disease that causes motor neuron (MN) degeneration and results in patient death within a few years. To recapitulate the cytopathies of ALS patients’ MNs, SOD1G85R mutant and corrected SOD1G85G isogenic-induced pluripotent stem cell (iPSC) lines were established. Two SOD1 mutant ALS (SOD1G85R and SOD1D90A), two SOD1 mutant corrected (SOD1G85G and SOD1D90D), and one sporadic ALS iPSC lines were directed toward MNs. After receiving ~90% purity fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…We found that gastrodin treatment increased the levels of p-ERK and p-JNK and reduced the level of p-GSK-3β, while t-ERK, t-GSK-3β and t-JNK remained stable compared to the control group. Our results are in line with earlier findings of the gastrodin effect mediated via downregulation of GSK-3β phosphorylation [26,35,48,78,79] and upregulation of ERK1/2 phosphorylation [34,46,47,78,80,81] in AD cellular and animal models. Intraneuronal…”
Section: Discussionsupporting
confidence: 93%
“…We found that gastrodin treatment increased the levels of p-ERK and p-JNK and reduced the level of p-GSK-3β, while t-ERK, t-GSK-3β and t-JNK remained stable compared to the control group. Our results are in line with earlier findings of the gastrodin effect mediated via downregulation of GSK-3β phosphorylation [26,35,48,78,79] and upregulation of ERK1/2 phosphorylation [34,46,47,78,80,81] in AD cellular and animal models. Intraneuronal…”
Section: Discussionsupporting
confidence: 93%
“…For MND modeling, we first generated an ALS iPSC line with the SOD1 G256C point mutation (SOD1 G85R ). In our previous study, we employed CRISPR/Cas9 gene editing to correct the SOD1 G256C mutant site to the normal nucleic acid, producing healthy SOD1 protein (SOD1 G85G iPSCs) [ 24 ]. In another previous study, we established an SFEB-based robust neuronal differentiation protocol known as the BiSF method to induce neuronal differentiation by adding FGFb, activin inhibitor SB, and Wnt ligand BIO ( Figure 1 a) [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…To evaluate the applicability of the CHSF-MN protocol on other PSC lines, two hESC lines, H9 (from WiCell; Figure 2 a–c) [ 30 ] and TW1 (established in Taiwan; Figure 2 d–f) [ 31 ]; and 5 ALS-related iPSC lines, SOD1 G85R ( Figure 2 g–i) [ 24 ], SOD1 G85G ( Figure 1 ) [ 24 ], SOD1 D90D (WiCell; Figure 2 j–l) [ 6 ], SOD1 D90A (WiCell; Figure 2 m–o) [ 6 ], and sporadic ALS ( Figure 2 p–r) [ 24 ] iPSC lines were directed toward MNs using this protocol. The differentiated cells expressed 95.43% ± 3.01% to 98.19% ± 1.05% Sox1 and 92.93% ± 1.36 to 98.13% ± 0.96% Oligo2 on day 15 with rosette-like structures in all hESC and iPSC lines ( Figure 2 s).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We steered the dissociated hPSCs differentiation to neural lineages by embryoid body (EB) formation 25 27 . In brief, the 1-2 × 10 5 /ml cells were cultured in Essential 6 medium (E6 medium, A1516401, Gibco) to form EB within the first 2 days.…”
Section: Methodsmentioning
confidence: 99%